EMERGENCY REMOTE TEACHING IN HIGHER HEALTH EDUCATION IN BRAZIL - Girardello, Débora Tatiane Feiber (2022)
Considering the legal proposals for the insertion of emergency remote teaching (ERT) as the most appropriate possibility, from a health point of view, during the Covid-19 pandemic for the continuity of didactic-pedagogical work in higher education, it becomes important to problematize how undergraduate health courses experienced the ERT in their training processes. In this sense, the objective was to systematize how the development of ERT in higher education was approached in scientific productions in the health area in Brazil during the pandemic. This is an integrative literature review, in the databases of Latin American and Caribbean Literature on Health Sciences (Lilacs), in the Nursing Database (BDENF) and in Medline via Pubmed, and in the Scientific Electronic Library Online (SciELO), using as keywords in Portuguese and English: Ensino Remoto Emergencial e Emergency Remote Teaching. Twelve articles were selected, produced between the years 2020 and 2021, which were systematized, which allowed the identification of two distinct themes in relation to the development of the ERE in higher education in health, namely: the impact of the ERT on academic training and proposals and didactic strategies for the ERT. Despite the limits experienced during the ERT, the impacts can be mitigated through strategies, didactic or institutional, which strengthen the teaching-learning process in health education. isolation and boosted the search for creative strategies for online classrooms, innovative technological strategies and auxiliaries to the teaching process used during the ERT.